Global‐Scale Shifts in Rooting Depths Due To Anthropocene Land Cover Changes Pose Unexamined Consequences for Critical Zone Functioning. Issue 11 (14th November 2022) - Hauser, Emma; Sullivan, Pamela L.; Flores, Alejandro N.; Hirmas, Daniel; Billings, Sharon A.
Abstract: Rooting depth is an ecosystem trait that determines the extent of soil development and carbon (C) and water cycling. Recent hypotheses propose that human‐induced changes to Earth's biogeochemical cycles propagate deeply into Earth's subsurface due to rooting depth changes from agricultural and climate‐induced land cover changes. Yet, the lack of a global‐scale quantification of rooting depth responses to human activity limits knowledge of hydrosphere‐atmosphere‐lithosphere feedbacks in the Anthropocene. Here we use land cover data sets to demonstrate that root depth distributions are changing globally as a consequence of agricultural expansion truncating depths above which 99% of root biomass occurs (D99) by ∼60 cm, and woody encroachment linked to anthropogenic climate change extending D99 in other regions by ∼38 cm. The net result of these two opposing drivers is a global reduction of D99 by 5%, or ∼8 cm, representing a loss of ∼11, 600 km 3 of rooted volume. Projected land cover scenarios in 2100 suggest additional future D99 shallowing of up to 30 cm, generating further losses of rooted volume of ∼43, 500 km 3, values exceeding root losses experienced to date and suggesting that the pace of root shallowing will quicken in the coming century. Losses of Earth's deepest roots—soil‐forming agents—suggest unanticipated changes in fluxes of water, solutes, and C. Two important messages emerge from our analyses: dynamic, human‐modified root distributions should be incorporated into earth systems models, and a significant gap in deep root research inhibits accurate projections of future root distributions and their biogeochemical consequences. Plain Language Summary: The distribution of plant roots helps determine the extent of nutrient, C, and water cycling beneath Earth's surface. Human activities, including land use and climate change, can change the distribution of plant roots and their activities across the globe. Here, we used global land cover data sets in combination with field‐generated rooting depth equations to estimate global scale changes to roots both now and into the future. Globally, roots are shallower than they would be in the absence of human activity due to extensive land conversion to agriculture. In some regions, human‐promoted woody encroachment induces root elongation, but this effect is overwhelmed by the spatial extent of agricultural conversion. In the future, roots likely will become shallower at an even faster pace. In future projections, deep roots appear especially vulnerable to loss, prompting numerous questions for additional field‐ and modeling‐based studies about the ways nutrients, C, and water will cycle in a future with fewer deep roots. We provide a foundation for those questions by demonstrating human influence on the roots that shape the character of Earth's skin. Key Points: Rooting depths are changing globally; the depth to which 99% of crop roots extend is shallower by ∼60 cm compared to natural systems In other regions, such as those experiencing woody encroachment, roots are deepening by ∼38 cm compared to previous dominant vegetation These opposing phenomena result in average rooting depths that are ∼8 cm shallower today and projected to become ∼30 cm shallower by 2100